2009
DOI: 10.1038/onc.2009.327
|View full text |Cite
|
Sign up to set email alerts
|

Cells deficient in the base excision repair protein, DNA polymerase beta, are hypersensitive to oxaliplatin chemotherapy

Abstract: A significant proportion of human cancers overexpress DNA polymerase beta (Pol b), the major DNA polymerase involved in base excision repair. The underlying mechanism and biological consequences of overexpression of this protein are unknown. We examined whether Pol b, expressed at levels found in tumor cells, is involved in the repair of DNA damage induced by oxaliplatin treatment and whether the expression status of this protein alters the sensitivity of cells to oxaliplatin. DNA damage induced by oxaliplatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 20 publications
2
37
0
2
Order By: Relevance
“…Moreover, JWA was shown to play a role in transcriptional and translational regulation of XRCC1 levels (18). XRCC1 is a critical component of the BER pathway, and downregulation of BER sensitized cancer to cisplatin or oxaliplatin (32,33). XRCC1 is also involved in NER (34), homologous recombination, and nonhomologous end joining (35,36), which are involved in platinum resistance (31).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, JWA was shown to play a role in transcriptional and translational regulation of XRCC1 levels (18). XRCC1 is a critical component of the BER pathway, and downregulation of BER sensitized cancer to cisplatin or oxaliplatin (32,33). XRCC1 is also involved in NER (34), homologous recombination, and nonhomologous end joining (35,36), which are involved in platinum resistance (31).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental evidence has linked expression levels of Pol-b, a key component of the BER pathway, to resistance to oxaliplatin across a panel of different cell lines, 207 but so far we lack data from clinical studies. BER however has an important role with respect to so-called 'synthetic lethality' through PARP inhibition; this topic is discussed below with respect to HRR.…”
Section: Base Excision Repairmentioning
confidence: 99%
“…The role in bypassing oxaliplatin-induced adducts in human DNA by DNA polymerases b, g, and h has also been postulated as a resistance mechanism. For example, overexpression of Polb-the major DNA polymerase involved in BER-or polh has been shown to confer resistance to oxaliplatin in colon and gastric cell lines, respectively (45,46). More recently, it has been observed that REV1 and Polz have a role in promoting both translesion DNA synthesis and DNA repair of damaged DNA after exposure to different platinum drugs, including oxaliplatin and in promoting resistance to these agents (47).…”
Section: The Glutathione Systemmentioning
confidence: 99%